Growth Inhibitory Property of Pentagamavunone-0 (PGV-0) on 4T1 Cells under Stress Condition : 2D and 3D Culture Model - Muflikhasari, Haruma Anggraini; Jenie, Riris Istighfari; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2019)
Pentagamavunone-0 (PGV-0), one of the curcumin analogue, is reported to have a cytotoxic effect on various cancer cells. This study aimed to explore the growth inhibitory effects of PGV-0 against highly-metastatic breast cancer, 4T1 cells under stress condition covering 2D and 3D speroid cytotoxic, anti-migration, and suppression of MMP-9. PGV-0 showed cytotoxic effects on 2D and 3D 4T1 cells with IC50value of 49 μM and 26 μM, respectively. In addition, PGV-0 performed anti-migratory effect. The single treatment at 25 μM PGV-0 and 50 μM showed inhibitory effect on cell migration by 54% and 51% respectively. whilst, the combination of PGV-0 at the concentration of 25 μM and 50 μM with doxorubicin significantly inhibited cell migration by 41% and 38%,  respectively. The gelatin zymography assay showed that PGV-0 decreased MMP-9 expression both in a single treatment and in combination with doxorubicin. In conclusion,  PGV-0 is potential to be developed as anti-tumorigenesis agent on highly-metastatic breast cancers.Keywords: Pentagamavunone-0 (PGV-0), anti-migration, MMP-9, 4T1 cells, spheroid